PERANCANGAN MEDIA PEMBELAJARAN MENGGUNAKAN SMART APPS CREATOR (SAC) DALAM APLIKASI AGRIFISH LEARN - Tubagus, Guntur Azhuri; Hutabarat, Rachel Merry Grace; Ghina Oktaviana Putri; Sukma, Nabilla Febrianty (Educational Technology Journal, 2025)
This study aims to develop an interactive digital learning medium called Agrifish Learn, which is specifically designed for vocational high school students in freshwater aquaculture agribusiness. This application was created using Smart Apps Creator (SAC) with a flowchart and storyboard approach to design navigation and visual and audio displays. The development model used is ADDIE, which includes the stages of needs analysis, interface design, content development, implementation, and evaluation through trials with ten vocational high school students. The resulting media consists of two main features: Material Pool and Quiz Pool, which present material and evaluation interactively. The results of the trials show that this media is easy to use, interesting, and helps students understand the material better.